Organised freethinking in Russia in large cities (with Moscow and St. Petersburg as examples) - Ekaterina Korostichenko; Valeriya Sleptsova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2020)
Our paper aims to present a comprehensive study of the present-day freethinkers in Moscow and St Petersburg. By means of a questionnaire-based survey (N=669), we analyse social and political attitudes and features of freethinkers’ worldview. The article proposes an operational defi nition of a freethinker. In compliance with this defi nition, we, for example, exclude from the study representatives of other faiths. Beside the analysis of the general sample, the article identifi es the specifi city of the organised freethinking in both capitals. Organised freethinking is represented by a number of public organisations and non-formal societies of cultural, educational, and social orientation whose aim is to criticise religion, church and to promote secular ideas in society. Apart from the questionnaire, we have used data of 14 interviews with leaders of organisations and with their active members. The data obtained by the questionnaire show that freethinkers do not make up a homogenous community, but are a milieu that consists of subgroups with diff erences in their worldview, political preferences, attitudes to religion and the church. The following previously observed regularities have been confi rmed: the freethinker is most often a man younger than 39, with a higher or incomplete higher technical education, with medium income. A signifi cant percentage of those inclined to superstitions shows a contradictory character of freethinkers’ worldview. Anticlerical and antireligious attitudes are rather strong, but the interviewees demonstrate tolerance towards religious persons. There is no signifi cant diff erences between those belonging to organisations and communities (N=150) and other freethinkers in terms of their social and demographic properties or views. But the organised freethinkers have a more active position as to defending their ideals in the Internet and in the public domain. Organised freethinking in both capitals is not a mass phenomenon. Despite the increase in the anticlerical attitudes in society, freethinkers are not eager to unite into organisations and are considerably disjointed.